FACTORS LIMITING USE OF ARTIFICIAL PULMONARY VENTILATION UNDER VOLUME CONTROL WHEN PERFORMING BRONCHOSCOPY WITH ENDOTRACHEAL TUBE (experimental research) - D. A. Averyanov; K. N. Khrapov; I. N. Grachev; K. A. Tsygankov (Вестник анестезиологии и реаниматологии, 2018)
The endoscopic monitoring when performing percutaneous dilatation tracheostomy requires continuous (up to several dozens of minutes) presence of fiberotic bronchoscope in the endotracheal tube. Under a certain proportion of the outer diameter of fiberotic bronchoscope and the inner diameter of the endotracheal tube it is not always possible to provide proper volume of the artificial pulmonary ventilation and it can result in the hypoventilation. Goal: using the lung model of TestChest® Respiratory Flight Simulator to define the most important factors limiting the increase of minute pulmonary ventilation (MPV) on APV during bronchoscopy through the endotracheal tube. Materials and methods: fiberotic bronchoscope of 5.9 mm outer diameter was put through endotracheal tube no. 8 which was pressure-proof installed to the inspiratory limb of the TestChest lung model with setup parameters reflecting the respiratory system of a patient with no disorders of respiratory mechanics. APV was under volume control. The respiratory volume was increased from 350 ml up to maximum with 25 ml step under the respiratory rate of 12, 16 and 20 respiratory movements per minute. Peak pressure, plateau pressure, autoPEEP, pressure behind the tip of endotracheal tube were registered before and after insertion of fiberotic bronchoscope. Results: increase of MPV was limited by the preset maximum pressure in the respiratory tract. Under the respiration rate of 12 movements per minute, MPV was 9.6 l/min; under the respiration rate of 16 movements per minute it was 12 l/min; under the respiration rate of 20 movements per minute it was 13.5 l/min. However, under the respiration rate of 12 movements per minute autoPEEP made 5 cm. w. c. with maximum MPV, and under the respiration rate of 16 and 20 movements per minute autoPEEP made even 14 and 24 cm. w. c. respectively. On the compared level of PEEP of 5 cm. w. c. MPV made 7.6 l. under the respiration rate of 16 movements per minute; and under the respiration rate of 20 movements per minute with the volume of 350 ml. the autoPEEP made 7 cm. w. c. Conclusion. Factors limiting MPV during APV in bronchoscopy through the endotracheal tube are peak pressure in the endotracheal tube and development of autoPEEP.